Pressure contact multi-chip packaging of SiC Schottky diodes - Gonzalez, Jose Ortiz; Alatise, Olayiwola; Mawby, Philip; Aliyu, Attahir Murtala; Castellazzi, Alberto (2017)
Pressure contact packages have demonstrated an improved reliability for silicon devices due to the elimination of the weak elements of the packaging, namely wirebonds and solder. This packaging approach has not yet been widely studied for SiC devices, however, it is of high interest for applications like HVDC or rail traction, where the wide bandgap properties of SiC devices can be fully exploited and high reliability is critical. Current IGBT press-pack modules use Si PiN diodes for enabling reverse conduction, however, the use of SiC Schottky diodes would be beneficial given their better characteristics including low switching losses and lower zero temperature coefficient (ZTC) for electrothermal stability of diodes in parallel. A prototype for the evaluation of SiC Schottky diodes using pressure contacts has been designed, built and tested for both single die and multiple die.